Odpowiedzi

2009-11-08T14:26:39+01:00
A) (x+2)(y+5)=xy+65
(x-5)(y-2)=xy-54


2x5y=65xy
5y=65xy+(-2x)
5y=63xy /xy
y=63


-5x+(-2y)=-54xy
-5x=-54xy-2y
-5x=52xy /-5
x=-10,4


b) 5x+2y=105
4,6x+2,4y=121,8

5x=105-2y
5x=103y /5
x=20,6


Najlepsza Odpowiedź!
2009-11-08T14:28:51+01:00
A) (x+2)(y+5)=xy+65
(x-5)(y-2)=xy-54

xy +5x+2y+10=xy+65(xy po obu stronach nam się uprosci)
xy-2x-5y+10=xy-54 (xy po obu stronach nam się uprosci)

5x+2y=55 *2 (mnozymy obustronnie)
-2x-5y=-64 *5

10x+4y=110
-10x-25y=-320
-----------------------------
10x +4y-10x-25y=-320 +110
-21y=-210 /-21
y=10

10x+ 4*10=110(podstawiamy do 10x+4y=110 aby wyliczyc x)
10x=110-40
10x=70 /10
x=7

b)5x+2y=105 *2,4
4,6x+2,4y=121,8 *-2

12x +4,8y=252
-9,2x-4,8y=-243,6
--------------------
12x +4,8y-9,2x-4,8y=252-243,6
12x-9,2x=8,4
2,8x=8,4
x=3
podstawiam x= 3 pod wyrazenie
5x+2y=105
czyli 5*3+2y=105
15+ 2y= 105
2y= 90
y=45